Potential Use of Insulin Patch Technology as Transdermal Drug Delivery in Efforts to Treat Diabetes Mellitus - PutrI, Nadya Aurelia Ratna; Harefa, Dellania Yvonne; Sianturi, Golda Santiur; Irawati, Wahyu (Universitas Brawijaya, 2022)
Diabetes Mellitus (DM) in Indonesia continues to increase from 2013 to 2018. Diabetes Mellitus is associated with the production of the hormone insulin in the cells of the pancreas. An increase in blood sugar levels can stimulate insulin secretion. There are several ways to treat Diabetes Mellitus, namely by using drugs, herbal methods, and insulin injections. In addition, one of the DM treatments that can reduce pain is using insulin patch technology as a transdermal treatment. The manuscript for this publication was made to find out the potential of using insulin patch technology as transdermal drug delivery to treat DM. Using a literature review research method that discusses four focus studies, including 1) the structure of the pancreas gland, 2) the mechanism of insulin hormone production by the pancreas gland, 3) the causes, symptoms, and conditions of patients with DM, and 4) insulin patch technology as a transdermal drug in the treatment of diabetes. DM treatment efforts. In the Langerhans section of the pancreas, some cells function to produce the hormone insulin. The amino acids that make up insulin are encoded by exons formed in insulin cells. Some causes of DM namely genetics, age, the influence of food, lack of physical activity, and an unhealthy lifestyle. Some of the symptoms, namely polyuria, polydipsia, polyphagia, etc. Patients with DM need insulin intake to help balance blood sugar levels, one of which is by using an insulin patch in which there is a microneedle containing insulin n-vinylpyrrolidone (NVP) and the enzyme glucose oxidase. After a literature review, it can be concluded that the insulin patch has excellent potential and promise because during the study tested on rats and pigs obtained good results and was able to lower blood sugar levels, although development is still needed. The manuscript of this publication still has shortcomings, so the author suggested to the next author to be able to multiply the latest sources related to insulin patch. Through the creation of the publication, the manuscript realized that diabetes mellitus is a form of human negligence in maintaining the body that God has designed carefully and regularly.